2020
DOI: 10.1029/2020gl089000
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Plasma Density Oscillation Related to EMIC Pc1 Waves

Abstract: We report the first observation of plasma density oscillations coherent with magnetic Pc1 waves. Swarm satellites observed compressional Pc1 wave activity in the 0.5–3 Hz band, which was coherent with in situ plasma density oscillations. Around the Pc1 event location, the Antarctic Neumayer Station III (L ~ 4.2) recorded similar Pc1 events in the horizontal component while NOAA‐15 observed isolated proton precipitations at energies above 30 keV. All these observations support that the compressional Pc1 waves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 36 publications
1
19
1
Order By: Relevance
“…This result is in contrast with the result of Kim et al. (2021) who reported using IPA crossing by the Swarm satellite in the ionosphere that the IPA was accompanied by weak upward/downward field‐aligned currents of 0.04–1 μA/m 2 . Nakamura et al.…”
Section: Event 1: Intermittent Weak Ipa On 22 April 2018contrasting
confidence: 99%
“…This result is in contrast with the result of Kim et al. (2021) who reported using IPA crossing by the Swarm satellite in the ionosphere that the IPA was accompanied by weak upward/downward field‐aligned currents of 0.04–1 μA/m 2 . Nakamura et al.…”
Section: Event 1: Intermittent Weak Ipa On 22 April 2018contrasting
confidence: 99%
“…Kim, Shiokawa, Park, Miyoshi, Miyashita, et al. (2020) found that Ne oscillation events and compressional waves tended to be in‐phase when the spectral intensity was higher and the wave frequency was lower. However, we did not find such linear correlation between the phases, spectral intensity, and wave frequency.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…Kim, Shiokawa, Park, Miyoshi, Miyashita et al. (2021) reported two cases of plasma density oscillation correlated with Pc1 wave, but a statistical study is still lacking. We have used 16 Hz Ne measurements from Swarm to perform this investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Kim, Shiokawa, Park, Miyoshi, Miyashita et al. (2021) studied the relationship between ionospheric EMIC parallel waves and electron density. They pointed out that the parallel wave occurred when Ne was >10 3.5 cm −3 .…”
Section: Discussionmentioning
confidence: 99%